With bonus interview of Martin E.P. Seligman. (Boston, Massachusetts, 2018)
Our professional lives are full of challenges and setbacks, but those who achieve elite performance are able to consistently rally their emotional strength in the pursuit of their goals--no matter what gets thrown at them. If you read nothing else on mental toughness, read these ten articles by experts in the field. We've combed through hundreds of articles in the Harvard Business Review archive and selected the most important ones to help you build your emotional strength and resilience--and to achieve high performance. This book will inspire you to: Thrive on pressure like an Olympic athlete Manage and overcome negative emotions by acknowledging them Plan short-term goals to achieve long-term aspirations Surround yourself with the people who will push you the hardest Use challenges to become a better leader Use creativity to move past trauma Understand the tools your mind uses to recover from setbacks.
Keywords: Leadership,Lãnh đạo; Psychological aspects,Khía cạnh tâm lý